A Green Approach for the Synthesis of Coconut Husk Ash –Twisted Graphene Nanocomposites: Novel Catalysts for Solvent‐Free Biginelli Reaction. Issue 16 (26th April 2019) - Narayanan, Divya P; Balasubramanyan, Sowmya; Cherikkallinmel, Sudha Kochiyil; Vadery, Vinu; Sankaran, Sugunan; Narayanan, Binitha N
Abstract: Herein we report an easy, scalable, cost‐effective and green synthesis of twisted graphene from bulk graphite by a ball milling technique with the in situ formation of novel coconut husk ash (CHA) ‐ twisted graphene nanocomposite and its catalytic application towards multicomponent Biginelli reaction. Here the ash derived from naturally available waste material (coconut husk) is effectively used as an exfoliating agent for the scissoring of graphene layers from bulk graphite for the first time. The elemental analysis data obtained by inductively coupled plasma atomic emission spectroscopy (ICP‐AES) provided useful information regarding the composition of CHA and the nanocomposites. The X‐ray diffraction (XRD) patterns confirmed the exfoliation of graphite into graphene layers. Raman spectroscopic analysis evaluated the quality and the nature of graphene layers in the composites. X‐ray photoelectron spectroscopy (XPS) analysis confirmed the bonding between the graphene layers and CHA particles. Transmission electron microscopy (TEM) images revealed the presence of few layered graphene as well as twisted graphene in the composites. The CHA – twisted graphene nanocomposite is found to be an excellent reusable catalyst for Biginelli reaction with a higher yield of 3, 4‐dihydropyrimidinones within short duration of reaction. Abstract : A novel coconut husk ash – twisted graphene nanocomposite has been prepared through an easy, scalable and cost‐effective greener approch by the ball mill assisted exfoliation of bulk graphite using coconut husk ash as a milling agent for the first time. The prepared nanocomposites are effectively used as excellent reusable catalysts in the multicomponent Biginelli reaction for the production of dihydropyrimidinones under solvent‐free reaction conditions.